2008
DOI: 10.1080/17453670710015030
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of leech therapy for knee osteoarthritis: A randomized study

Abstract: Leech therapy can reduce symptoms caused by osteoarthritis. Repeated use of the leeches appears to improve the long-term results. We have not determined whether the positive outcome of the leech therapy is caused by active substances released during the leeching, the placebo effect, or the high expectations placed on this unusual treatment form.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
5

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(29 citation statements)
references
References 30 publications
0
24
0
5
Order By: Relevance
“…tedavi amaçlı aktif olarak çeşitli klinik durumlarda apse, artrit, glokom, myasthenia gravis, dental tedaviler, hematom, tromboz, gangrene gidişin önlenmesi ve diğer çeşitli damar bozukluklarında (arteriyoskleroz, diabetik damar komplikasyonları, varisler, diğer kardiyovasküler hastalıklar…) tıbbi tedaviye yardımcı olarak çeşitli kliniklerde (kardioloji, jinekoloji, üroloji, cerrahi, travmatoloji, stomatoloji, oftalmoloji vb.) hirudoterapinin kullanımı artmaktadır (1,14,32,(37)(38)(39)(40).…”
Section: Hirudoterapinin Endikasyonlarıunclassified
“…tedavi amaçlı aktif olarak çeşitli klinik durumlarda apse, artrit, glokom, myasthenia gravis, dental tedaviler, hematom, tromboz, gangrene gidişin önlenmesi ve diğer çeşitli damar bozukluklarında (arteriyoskleroz, diabetik damar komplikasyonları, varisler, diğer kardiyovasküler hastalıklar…) tıbbi tedaviye yardımcı olarak çeşitli kliniklerde (kardioloji, jinekoloji, üroloji, cerrahi, travmatoloji, stomatoloji, oftalmoloji vb.) hirudoterapinin kullanımı artmaktadır (1,14,32,(37)(38)(39)(40).…”
Section: Hirudoterapinin Endikasyonlarıunclassified
“…The study did not report any other complication or infection. [12] A common minor side effect of mild itching at the site of leech bite lasting for a mean of 4 days was recorded by Zaidi et al They reported a slight but clinically non-relevant decrease in hemoglobin levels after leeching. [2] Shiffa et al did not report any adverse side effects in any of the 30 patients of test group.…”
Section: World Journal Of Pharmaceutical Researchmentioning
confidence: 99%
“…to achieve a better long term effect. [2,10,12] Although Leech therapy can be used in the symptomatic management of knee osteoarthritis a number of queries are still to be investigated and answered. The optimal number of leeches to be applied, maximum or minimum time of application, site of application and frequency of application is still not well defined and needs further studies.…”
Section: World Journal Of Pharmaceutical Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…Many clinical studies and case reports have examined the usage of LT against pain, but these were mainly focused on symptomatic treatment of knee osteoarthritis (11)(12)(13)(14)(15)(16). A single course of LT has been shown to provide symptomatic relief and improvement in functional ability and quality of life in women with symptomatic arthritis in their carpometacarpal joint for at least two months (17).…”
Section: Introductionmentioning
confidence: 99%